FX Swaps : Implications for Financial and Economic Stability - Ong, Li (IMF Working Papers; Working Paper ;, 2010)
The proliferation of foreign exchange (FX) swaps as a source of funding and as a hedging tool has focused attention on the role of the FX swap market in the recent crisis. The turbulence in international money markets spilled over into the FX swap market in the second-half of 2007 and into 2008, giving rise to concerns over the ability of banks to roll over their funding requirements and manage their liquidity risk. The turmoil also raised questions about banks' ability to continue their supply of credit to the local economy, as well as the external financing gap it could create. In this paper, we examine the channels through which FX swap transactions could affect a country's financial and economic stability, and highlight the strategies central banks can employ to mitigate market pressures. While not offering any judgment on the instrument itself, we show that the use of FX swaps for funding and hedging purposes is not infallible, especially during periods of market stress.